Constructing a nation branding model – the case of Serbia - Novčić Korać, Branka; Bradić-Martinović, Aleksandra; Miletić, Branislav (Geographica Pannonica, 2020)
This paper aims to understand the concept and fundamental terms related to nation branding as a strategic tool for improving Serbia’s international market position, a post-communist and former Yugoslav country. The author intends to gain insight into Serbia’s current brand perception as a developing country that can find an opportunity for rebirth and parting with the legacy implementation of the nation branding concept. The quantitative research methods were applied in this paper, and the questionnaire developed for the research investigated the perception of brand Serbia by leaning on Risitano’s framework. Our analysis finds that national treasury, people, tourism and business destination were recognized as the most important points for country and nation positioning.
Keywords: nation brand; Serbia; branding model; tourism